2002
DOI: 10.1002/fld.372
|View full text |Cite
|
Sign up to set email alerts
|

A fast Godunov method for the water‐hammer problem

Abstract: SUMMARYAn e cient Godunov-type numerical method with second-order accuracy was developed to simulate the water-hammer problem in piping. The exact solutions of the Riemann problem were analysed and illustrated on the intriguing solution diagram by properly introducing dimensionless variables within reasonably practical ranges. Based on the solution diagram, an e cient fast Riemann solver was also developed. Moreover, small perturbation analysis was performed to demonstrate the relations between the primitive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…FV methods can also be used for water hammer simulations. Guinot [17], Hwang and Chung [18], Zhao and Ghidaoui [19], León et al [20], and Sabbagh-Yazdi et al [21] formulated first-and second-order explicit FV methods of the Godunov type for solving water hammer problems. All these studies concluded that second-order Godunov-type methods are more accurate and faster.…”
Section: Introductionmentioning
confidence: 99%
“…FV methods can also be used for water hammer simulations. Guinot [17], Hwang and Chung [18], Zhao and Ghidaoui [19], León et al [20], and Sabbagh-Yazdi et al [21] formulated first-and second-order explicit FV methods of the Godunov type for solving water hammer problems. All these studies concluded that second-order Godunov-type methods are more accurate and faster.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the FSI with water hammer in the pipeline is calculated. It achieves dispersion of the equations with the control volume integral and integrates the continuous equation from t to t + ∆t [32,33]. From Equations (1)-(8), the continuity and momentum equations of the water region and structure region can be written in the matrix form.…”
Section: Finite Volume Methodsmentioning
confidence: 99%
“…However, non-conservative hyperbolic systems can be solved quite accurately with a similar characteristic upwind finite-difference numerical method that relies on a less accurate treatment of the discontinuities . Numerical tests with WAHA code demonstrated that shock waves in nearly incompressible liquid obtained with the characteristic upwind and the non-conservative numerical schemes are practically equal to the shock waves calculated from the Godunov-type methods relying on the exact Rankine-Hugoniot condition (see Tiselj and Petelin, 1997;Guinot, 2002;Hwang and Chung, 2002;Zhao and Ghidaoui, 2004). The numerical scheme of the test code used herein is almost the same as the numerical scheme of the WAHA code, such that only a summary is given here.…”
Section: Characteristic Upwind Finite-difference Schemementioning
confidence: 96%